Carbon nanotubes/chitin nanowhiskers aerogel achieved by quaternization‐induced gelation. Issue 37 (18th June 2015) - Garcia, Ignacio; Azcune, Itxaso; Casuso, Pablo; Carrasco, Pedro M.; Grande, Hans‐J.; Cabañero, Germán; Katsigiannopoulos, Dimitrios; Grana, Eftychia; Dimos, Konstantinos; Karakassides, Michael A.; Odriozola, Ibon; Avgeropoulos, Apostolos
ABSTRACT Organic aerogels from polysaccharides such as cellulose and chitin are of particular importance because they utilize renewable feedstocks. In this article, the aerogels were prepared through the self‐assembly of chitin nanowhiskers previously modified. The surface of chitin nanowhiskers was rendered cationic through two reactions. A first reaction between hydroxyl groups of chitin and 2‐chloroethyl isocyanate and a second reaction between the chloride groups of isocyanate anchored to the surface and 1‐methylimidazole. This modification led to stable aqueous suspensions of the chitin nanowhiskers with gelation and rheological properties. Additionally, chitin nanowhiskers aerogels containing modified carbon nanotubes were obtained. The addition of modified carbon nanotubes provoked a change in the morphology of the hydrogels and as a consequence, the rheological properties of the hydrogel are modified as well. In contrast from previous procedures, this method has not required any kind of solvent exchange or high pressure in order to obtain the final materials. © 2015 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2015, 132, 42547.